Джерела інвестиційного забезпечення інформаційних технологій - Горбова, Христина (Видавництво «Редакція «УП», 2016)
The basic principles of investment security of information technology, ways to attract investments and risks that arise with the proposed ways to improve investment in information technology.
Keywords: інвестиції; інформаційні технології; підприємство; ризик; ефективність